(3GdOjGQGJs - (3Ydj Hf eMeO GdTGHTJj, CHh GdMSf,J (B388 (3g` s ((3GHf eMeO Hf YHO GdhgGH Hf CMeO Hf ZQHi GdOeTbi GdeYQha LOg HGdfMhi s)
(3ChdgG (B:s
(3OjQ OQeGdS s
(3fSNI eUhQI Yf fSNI HQdjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B325 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B202s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B135 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJGQjNs